New Reality – New Problems. Financial Crime in Greater Poland in the Years 1945-1970 - Jankowiak, Stanisław (Studia Historiae Oeconomicae, 2016)
Systemic transformation in Poland after the Second World War led to deep transformations within the economy. It did not, however, change the way people thought. Despite the chaos of the post-war period, in which all the negative features shaped in the period of occupation manifested themselves, it seemed that the conceptual leaders of the Polish political and economic life would create new quality. However, it soon turned out that old habits die hard and the system created by communists opened a field for many abuses. This was accompanied by a sense of impunity, as the most prominent personalities in a given region were also involved in economic scandals. All this resulted in the creation of “cliques” in which both prominent Party activists and people put by the Party in high positions (usually also members of the Polish United Workers’ Party, PUWP) played important roles. On the one hand, after 1956, surveillance by the Security Office (UB) or Security Services (SB) was not that strict anymore, and on the other, the so-called “private initiative” started to develop fast – therefore the more “entrepreneurial” individuals started to exploit the situation and gain wealth. Abusing one’s position to organize large-scale thefts was considered relatively normal. This happened in various forms: sometimes directly, but more often by supporting or even organizing private projects with the use of the national, though unsupervised, supply of raw materials or products. This way, the Party members grew richer at the expense of the companies they worked for. This business was relatively widely tolerated by ordinary citizens, who saw it as an excuse to also “organize” goods individually for their own purposes in the companies which employed them. This common belief that “everybody steals” allowed people to justify their own dishonesty. Any attempts to fight this problem failed to produce satisfactory results. The diagnosis, even if correct, had to face reality, in which the pursuit of a better quality of life by the Party elites collided with the officially promoted ascetic lifestyles of the “ideological communists”, who, like Władysław Gomułka, did not understood the new times.